PENGARUH KEPUASAN PELANGGAN MARKETPLACE DAN FINTECH TERHADAP PENJUALAN UMKM KULINER DI KOTA BANDUNG (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2023)
The outbreak of the Covid-19 virus in Indonesia has an impact on the decline in sales turnover of Micro, Small, Medium Enterprises (MSMEs), especially in the culinary field. Thus, MSMEs need a strategy in order to maintain their efforts, one of which is the use of technology in the form of marketplaces and financial technology. This study was conducted to analyze the effect of market customer satisfaction and the use of financial technology on increasing sales of culinary SMEs in Bandung City. This research is a quantitative descriptive study using primary data, collected through questionnaires distributed in a mixed manner. The population in this study is culinary SMEs in the Bandung City area with a total sample of 100 respondents. The analytical method used is path analysis using the SPSS version 26 program. The results of this study indicate that market customer satisfaction partially has a positive and significant effect on increasing MSME sales, while the use of financial technology partially has no effect on increasing MSME sales, and simultaneously marketplace customer satisfaction and the use of financial technology have a positive and significant impact on increasing MSME sales.